A case report study of Intrabony Neurofibroma - N. Eshghyar; N. Taghva Gasemiyan (Tehran University of Medical Sciences, 1996)
Intrabony neurofibroma is a very rare lesion (6% of all types of neurofibroma) and in 80% of cases it is seen in spine. Current study is aimed to analyze the published articles in this field as well as presenting a rare case.